Sources of Stress among Medical Students - Mudasar Zia, Anoosh Qayyum, Sadia Majeed, Maheen Saad, Farah Hanif, Shazia Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out the frequency and relative frequency of stress on medical students of a local medical college, Lahore. Study Design: Cross sectional study Place and Duration of study: Local Medical College with duration one month (Feb 2019) Methods: The study was surveyed on 150 medical students of M.B.B.S part 1 & 11. Questionnaire was divided into three sections including environmental stress, family affairs stress and stress of studies. Results: In the context of environmental stress features in medical students the highest odds of stress in students was problem in time management for study, followed by feeling of bullying and their current feelings of stress, feeling of uncomfortable at the time of dissection and conflict with other student. In the context of stress the highest odds of stress was due to family affairs in medical students was responsibility in regard to family problem, family issues, history of family depression and recently loss of family member. The last context was study related stress include the highest odds of stress in students who not fulfill self-expectations and fail to perform task followed by poor in the studies due disturbances by the class fellows, ineffective copying skills and non-serious attitude toward studies followed by emotional stress and sleeping. Conclusion: It is concluded that good academic environment, as well as problem focused and emotion focused strategies may help to alleviate stress.